Research in law and economics a journal of policy - Zerbe, Richard O. (Research in law and economics ;, 2007)
Since 1979 Research in Law and Economics has been presenting original research that explores the extent to which the constraints of law explain economic behavior and the role of economics in forming the law. Leading scholars, including Kenneth Arrow, Kenneth Elzinga, Victor Goldberg, Jack Hirschliefer, Paul Joskow, and Vernon Smith, have chosen Research in Law and Economics as the right forum for presenting their research. Now published bi-annually, each issue of Research in Law and Economics focuses on a timely and relevant topic. Such topics have included economics of environmental policy, urban property rights, antitrust and evolutionary models in economics and law. This volume focuses on cost-benefit analysis and the law, whereas the next special issue will concentrate on corporate finance.